EVALUATION OF PREVENTIVE PROCEDURES FOLLOWED BY SAUDI DENTISTS AGAINST COVID-19 - Alotaibi, May Mansour; Alotaibi, Maha Mansour; AlRajhi, Asma Saleh; AlSudairy, Sultanah Abdulmehsen; Alanazi, Mona Dabshi (Journal of medical and pharmaceutical sciences, 2021)
The study aimed to identify the investigation of the situation on the preventive measures that Saudi dental practitioners followed during the Coronavirus (Covid-19) pandemic in four major cities in Saudi Arabia, which are the capital, Riyadh, Jeddah, Makkah and Madinah, and the study was limited to current dental practitioners who provide medical care In hospitals and dental clinics, and the study sample did not include university professors or dental students, and through this study we sought to know the preventive measures that dental practitioners followed by following the recommendations and guidelines of the World Health Organization regarding preventive measures for dental professionals to prevent Coronavirus (Covid-19). While the questionnaire was designed using the G-Forms application, and the questionnaire was sent to remote dental practitioners via the Internet through applications and social networking sites, total of study sample (525), 235males and 290 females The results of the study showed that Saudi dentists followed the guidelines and recommendations of the World Health Organization to confront the Coronavirus (Covid-19), as Saudi dentists showed a high commitment to wearing mask, wearing gloves, sterilizing all medical devices before and after providing patient care, Directing all persons attending the clinic to wear masks, asked all patients upon attending if they have a symptoms consistent with COVID-19, Handwashing with soap and water or alcohol-based hand sanitizer for everyone, checking the patient’s temperature by digital thermometer, and screening patients by virtual/remote technology or telephone. While the results showed a decline in some preventive measures followed by Saudi dentists such as: wearing protective outerwear, using rubber dams, use a mouthwash that contains chlorhexidine, and wearing shoe covers. Based on the results of the study, the percentage of self-evaluation of preventive measures followed by dental practitioners ranged from 70-80%